Fitting the frequency-dependent parameters in the Bergeron line model - Caballero, Pablo Torrez [UNESP]; Marques Costa, Eduardo C. [UNESP]; Kurokawa, Sergio [UNESP] (Elsevier B.V., 2014)
A new transmission line modeling - TLM is proposed based on the well-established Bergeron method. The conventional Bergeron model is characterized by the line representation through concentrated longitudinal and transversal parameters, i.e., the line electrical parameters are represented by means of electric circuit elements R, L, G and C. The novel approach of this research is the inclusion of the frequency effect in the longitudinal parameters in the Bergeron line representation. This new feature enables to extend the application of the Bergeron method for simulations of transients composed of a wide range of frequencies. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bergeron line model; Transmission line modeling - TLM; Electromagnetic transients; Time-domain analysis; Frequency-dependent parameters; Power system modeling